Analysis of School Environment Development Activities on the Formation of Children's Naturalistic Intelligence at Pertiwi Panggung Kindergarten. - Rohmania, Roudhotur (Jurusan Pendidikan Islam Anak Usia Dini UIN Sunan Gunung Djati Bandung, 2024)
This study aimed to analyze the impact of healthy environment development activities at TK Pertiwi Panggung on the formation of children's naturalistic intelligence. Environmental education is crucial in early childhood as it plays a role in fostering ecological awareness and an attitude of caring for the environment. The activities implemented included gardening, waste sorting, and maintaining cleanliness, which directly provided nature-based learning experiences for the children. The research method used was descriptive qualitative, with data collection through observation, interviews, and documentation. The results indicated that the healthy environment development activities not only enhanced children's naturalistic intelligence but also instilled discipline, responsibility, and a love for nature. Some challenges faced included limited space and parental support. Additionally, the active involvement of teachers in facilitating these activities had a significant impact on the success of the program. In conclusion, the healthy environment development program at school plays a significant role in shaping children's naturalistic intelligence and fostering environmental care characteristics in early childhood. This highlights the importance of integrating environmental education into early childhood education curricula to support the holistic development of character and intelligence.